1995
DOI: 10.1002/pssb.2221920105
|View full text |Cite
|
Sign up to set email alerts
|

Could the Oxygen Vacancy in Oxides of the Perovskite Family Be a Dipole Center?

Abstract: The lattice polarization in oxides of the perovskite family is demonstrated to give rise to symmetry breaking of one-electron orbitals at F centers. This can provide an explanation of recent experiments on paraelectric KTaO, where, by the second harmonic generation method, approximately lo'* cm-3 dipole centers were found, the concentration of which depends on reduction and oxidation processes. I) Sorge str. 5, 344 104 Rostov-on-Don, Russia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
10
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
4
10
0
Order By: Relevance
“…Later on, theoretical studies performed in the framework of a Green function approach considered possible reasons for such symmetry breaking. 3,4 Within that study the electron's activation energies were obtained in accordance with data on electroconductivity 5 which we will discuss below.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…Later on, theoretical studies performed in the framework of a Green function approach considered possible reasons for such symmetry breaking. 3,4 Within that study the electron's activation energies were obtained in accordance with data on electroconductivity 5 which we will discuss below.…”
supporting
confidence: 59%
“…Theoretical studies 3,4 did not consider the states of the F -center-type (a vacancy centered, symmetric electron density), but, later, computations showed that the states of the F -center type , in the single charged oxygen vacancy (V + O ), can have lower energy than the states of the V ++ O Ti 3+ -type 6,7,8 . However, the EPR signal of such states has not been found experimentally.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All these studies were performed on the assumption that the symmetry of V O coincides with the point symmetry of the oxygen site in the ideal crystal. However, recently, it was shown that the single-charged V + O may be a dipole centre [12][13][14][15]. In this case, an electron captured by V O predominantly localizes on one of the neighbours to the V O ions.…”
Section: Introductionmentioning
confidence: 99%
“…The observation of the Fano effect, and the suggestions based on it that local polar regions exist in STO thin films, may hold the key to the understanding of the lattice dynamical and dielectric properties of ferroelectric thin films. The existence of such local polar regions around defects or oxygen vacancies has been proposed in bulk materials both experimentally [27,28,44,56] and theoretically [57][58][59].…”
Section: Discussionmentioning
confidence: 97%